Teachers, Schools, and Pre-K Effect Persistence: An Examination of the Sustaining Environment Hypothesis. Issue 4 (1st October 2020) - Pearman, Francis A.; Springer, Matthew P.; Lipsey, Mark; Lachowicz, Mark; Swain, Walker; Farran, Dale
Abstract: The sustaining environments thesis hypothesizes that PreK effects are more likely to persist into later grades if children experience high-quality learning environments in the years subsequent to PreK. This study tests this hypothesis using data from a statewide PreK randomized experiment in Tennessee that found positive effects at the end of PreK that did not persist past kindergarten. These data were combined with teacher observation and school-level value-added scores from Tennessee's formal evaluation system to determine whether positive effects of PreK persisted for the subgroup of students exposed to higher-quality learning environments between kindergarten and 3rd grade. Neither exposure to highly effective teachers nor attending a high-quality school was sufficient by itself to explain differences in achievement between PreK participants and non-participants in 3rd-grade. However, this study found evidence that having both was associated with a sustained advantage for PreK participants in both math and ELA. Notably, however, very few children were exposed to high-quality learning environments after PreK, suggesting that maximizing PreK investments may require attending to the quality of learning environments during PreK and beyond.